CLE peptides join the plant longevity club. (October 2022) - Han, Huibin; Zhuang, Keqing; Qiu, Ziwen
Abstract : Leaf senescence, the final step of leaf development, is an essential adaptive process that involves intricate regulatory networks mediated by various developmental and environmental clues. Two recent reports, by Zhang Z. et al. and Zhang Y. et al., shed light on how CLE peptides recruit reactive oxygen species (ROS) and ethylene signaling to promote plant leaf longevity.